Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey - Dogan, Sibel; Dogan, Salih; Erman, Orhan (Magnolia Press, 2017)
Five new species of Stigmaeidae (Acariformes: Raphignathoidea) from Harsit Valley and Orumcek Forests (Turkey) are described: Stigmaeus communis sp. nov., S. fimus sp. nov., S. harsitensis sp. nov., S. longiclipeatus sp. nov., and S. pseudoparmatus sp. nov.
Keywords: Raphignathoidea; soil mites; systematics; Harsit Valley; Orumcek Forests